Age-appropriate vaccination coverage and its determinants for the polio containing vaccine 1-3 and measles-containing vaccine doses in Zhejiang province, China: A community-based cross-sectional study - Yu Hu; Yaping Chen; Ying Wang; Hu Liang; Huakun Lv (Taylor & Francis Group, 2020)
Background: This study aimed to evaluate the age-appropriate coverage and its associated risk factors for the primary vaccination of Polio containing vaccine (PCV) and measles-containing vaccine (MCV) through the secondary use of the 2018 Zhejiang provincial coverage survey among children aged 12-23 months. Methods: Data were collected through structured pre-tested Chinese version questionnaire by face-to-face interview among 770 mothers whose children aged 12-23 months. Age-appropriate vaccination coverage was measured using Chinese vaccination schedule recommendation. Bivariate and multivariate logistic regression models were adopted to identify determinants of the age-inappropriate vaccination. Results: The age-appropriate vaccination coverage of PCV1, PCV2, PCV3, and MCV was 88.8%, 80.8%, 73.6%, and 75.7%, respectively. The risk factors associated with the age-inappropriate vaccination of PCV 1-3 dose and MCV included child's gender, birthplace, living area, maternal education level, immigration status, monthly household income, participation of the pregnant women's seminar, antenatal care follow-up, knowledge on vaccination. Conclusion: The proportions of age-appropriate vaccination coverage were low compared with the up-to-date coverage. Modifiable factors were associated with age-inappropriate vaccinations. Vaccination interventions should consider identified modifiable factors to improve age-appropriate vaccination coverage.